Pelatihan Teknik Pengemasan dan Pemasangan Label Produk Masker Bubuk Bayam sebagai Upaya Peningkatan Keterampilan Mahasiswa dalam Strategi Branding Produk - Alya Salwa Aqila; Anggit Dyah Kusumastuti (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
The development of natural skincare products, such as spinach powder face masks, is becoming increasingly popular as a safe and environmentally friendly alternative. However, many beginner entrepreneurs lack understanding of proper packaging and labeling techniques, which can reduce product appeal and consumer trust. This community service activity aimed to enhance students’ skills in applying effective packaging and labeling techniques as part of product branding strategies. The implementation methods included knowledge delivery through training sessions, literature review on cosmetic packaging standards, creative design of attractive packaging and labels, and hands-on practice in packaging and labeling the spinach powder face mask products. The results showed that students gained new insights into the importance of packaging and labeling in building brand image. Moreover, the professionally designed packaging and informative labels created by the students successfully improved the perceived quality of the product among consumers and increased its marketability.